2017
DOI: 10.5455/medscience.2016.06.8633
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy and associated factors in people living in a nursing home in Kayseri Turkey

Abstract: It has been found that residents of nursing homes have more frequent drug side effects, because they use more drugs than those living in the community. This study was conducted to determine the status of polypharmacy and related factors among the individuals living in a nursing home. Materials and Methods: The cross-sectional study was conducted in a nursing home in the provincial centre of Kayseri in 2016. A socio-demographic questionnaire and Standardized Mini Mental Test (SMMT) were used for data collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…In community-based telephonic survey conducted in 1998 and 1999 in the USA, 10 the rates of polypharmacy and excessive polypharmacy were reported to be 57% and 12% in elderly females and, 44% and 12% in elderly males, respectively. Moreover, the rate of polypharmacy was reported to be 59.6% in a study conducted in patients living in a nursing home in Turkey, 11 26.7% in a study conducted in 67 primary care practices in Germany, 12 47.6% in a study on female patients in a geriatric outpatient clinic in Turkey, 13 and 45% in a study on patients aged ≥75 year-old who were admitted to the emergency services in England. 14 In the case of hospital-based studies, in a study on patients admitted to 5 hospitals in Norway, 15 the rate of polypharmacy on admission was reported to be 47%.…”
Section: Discussionmentioning
confidence: 99%
“…In community-based telephonic survey conducted in 1998 and 1999 in the USA, 10 the rates of polypharmacy and excessive polypharmacy were reported to be 57% and 12% in elderly females and, 44% and 12% in elderly males, respectively. Moreover, the rate of polypharmacy was reported to be 59.6% in a study conducted in patients living in a nursing home in Turkey, 11 26.7% in a study conducted in 67 primary care practices in Germany, 12 47.6% in a study on female patients in a geriatric outpatient clinic in Turkey, 13 and 45% in a study on patients aged ≥75 year-old who were admitted to the emergency services in England. 14 In the case of hospital-based studies, in a study on patients admitted to 5 hospitals in Norway, 15 the rate of polypharmacy on admission was reported to be 47%.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of drugs, the most common of these was the inappropriate use of proton pump inhibitors (PPI) (n=30, 9.9%) and potent anticholinergics (n=23, 7.6%). The rates of polypharmacy were reported as 47.6% in a study that patients admitted to a geriatric outpatient clinic in Turkey 5 , 59.6% in a study that patients living in nursing homes in Turkey 6 , 47% in a study that patients admitted to the hospital in Norway 7 and 51.9% in another study in Italy. 8 The rates of PIDs in studies using Beers 2015 criteria were reported as 60% in a study in two assisted living facilities in the USA 9 and 29.3% in another study at the time of admission to internal medicine and surgical services in Jordan, and in the latter study PPIs were the most common PIDs.…”
mentioning
confidence: 97%